Reduce the Pollution of Some Heavy Elements in Agricultural Soil by Biological Treatment of Certain types of Algae - Ibtisam Fareed Ali Karm (Journal of Global Pharma Technology, 2018)
Many researches on soil contamination had been done but few solutions were offered. This research focused on the use of some microorganisms as an alternative ways for remediation environmental pollution to reduce the concentration of five heavy elements that were tested Pb, Cd, Cr, Ni and Cu. Therefore, this research was conducted in order to find out the effect of mixed algae culture from two important microalgae (Oscillatoria sp. and Chlorella sp. ) that were locally isolate and cultivated easily under lablotary conditions to give a biomass production , a laboratory experiment was done for 12  samples of contaminated soil with heavy metals. Testing the bioactivity of remediation take three weeks, a significant difference were recorded in some data treatments, others show no significant, in general all concentrations of heavy metals were degreased after using the mixed algae culture that chosen for its wide ability for cleaning or removing the pollutants from agriculture soils. Keywords:  Mixed algae culture, Agriculture soils, Heavy metals, Bioremediation.